Managing human capital in today's globalization : a management information system perspective - Susanto, Heru, 1965-; Leu, Fang-Yie; Chen, Chin Kang (Toronto ; New Jersey : Apple Academic Press, 2019)
This book explores important issues in human capital in human resource management as it relates to management information systems (MIS). It highlights how management information systems are implemented and the potential for employee resistance, offering behavioral strategies to involve employees in adopting effective MIS and in overcoming resistance during change. The authors also look at the available research that focuses on the changing skills requirements of employees in the context of both MIS perspectives and HRM perspectives. They address how current trends have evolved into a hyper-emerging market of competitive advantage and fast-changing environments toward globalization. The authors also address: workforce planning and management systems strategic human resource management re-engineering work processes for improved productivity work-force diversity the integration of MIS-HRIS and employee involvement human resource globalization and MIS implications the impact of digital technology on decentralized work sites organizational continuous improvement programs
Workforce Planning and Management Systems: HRIS Approach -- Strategic Human Resource Management: An ICT Possibility Shifting Paradigm of Human Resource Management -- Managing Information Systems for Human Resource Management: A Technological Evolution -- Changing Skill Requirements: Improving Market Expectation of Human Resource Management -- Human Resource Management Information System: The Challenges -- The Shifting Paradigm of Human Resource Management Through a Human Resource Management Information System -- Re-Engineering Work Processes for Improved Productivity: A Management Information System Perspective -- Workforce Diversity: Information Communication Technology Innovation and Creativity -- A Management Information System for Human Resource Management: Workforce Diversity -- The Integration of MIS-HRIS and Employee Involvement -- Human Resource Globalization and MIS Implications -- Digital Technology Impact on Decentralized Work Sites -- Organization Continuous Improvement Programs: MIS Technological Advancement -- Continuous Improvement Programs: The Digital Technology Era ofHuman Resource Management.
OCLC-licensed vendor bibliographic record.
Keywords: Personnel management -- Technological innovations; Management information systems; BUSINESS & ECONOMICS / Human Resources & Personnel Management; BUSINESS & ECONOMICS / Information Management; SCIENCE / General